2017
DOI: 10.1177/1052562917727797
|View full text |Cite
|
Sign up to set email alerts
|

Management Education and Transformational Learning: The Integration of Mindfulness in an MBA Course

Abstract: Most management classes are taught by modified traditional techniques in which the acquisition of facts and rote skills is primary. However, traditional pedagogies fall short when the desired result is not inculcating knowledge about a subject, but rather constructively altering worldviews and behaviors. Leadership, ethics, strategic management, and communications are some of the subjects for which worldview change is imperative and traditional, knowledge-inculcating pedagogies are inadequate. The type of cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 63 publications
1
31
0
2
Order By: Relevance
“…The results have shown that mindfulness improves self-control abilities and awareness (e.g., [50]), increases self-efficacy (e.g., [25,51]), coping strategies (e.g., [52]), that are connected with resilience, enhances attentive skills (e.g., [53]), improves cognitive performance and metacognition (e.g., [54]), and decreases stress, anxiety, and depression (e.g., [47,[55][56][57][58]). As a consequence, it is not surprising that mindfulness-based training has been introduced permanently in several universities around the world [40,43,59,60].…”
Section: Mindfulnessmentioning
confidence: 99%
“…The results have shown that mindfulness improves self-control abilities and awareness (e.g., [50]), increases self-efficacy (e.g., [25,51]), coping strategies (e.g., [52]), that are connected with resilience, enhances attentive skills (e.g., [53]), improves cognitive performance and metacognition (e.g., [54]), and decreases stress, anxiety, and depression (e.g., [47,[55][56][57][58]). As a consequence, it is not surprising that mindfulness-based training has been introduced permanently in several universities around the world [40,43,59,60].…”
Section: Mindfulnessmentioning
confidence: 99%
“…Leadership and business educators have also advocated for mindfulness training (Dumas, 2007;Kuechler & Stedham, 2018;Reitz & Chaskalsonas, 2016), suggesting that enhanced awareness of self and others helps leaders and students more effectively deal with complex and dynamic organizational realities. Business schools such as New York University's Stern School of Business have developed mindfulness initiatives to build students' leadership skills and enhance their emotional intelligence (Kim & Shy, 2015).…”
Section: The Concept Of Mindfulnessmentioning
confidence: 99%
“…Business schools such as New York University's Stern School of Business have developed mindfulness initiatives to build students' leadership skills and enhance their emotional intelligence (Kim & Shy, 2015). Other management educators have discovered that incorporating mindfulness into the business curriculum increased students' acceptance of novel perspectives (Kuechler & Stedham, 2018). Relative to leadership development, studies suggest training and practice in mindfulness resulted in increases in leader resilience, the capacity for collaboration, and the ability to lead in complex conditions (Reitz & Chaskalson, 2016).…”
Section: The Concept Of Mindfulnessmentioning
confidence: 99%
See 2 more Smart Citations